Hypertext or Textbook: Effects on Motivation and Gain in Knowledge - Cathérine Conradty; Franz X. Bogner (MDPI AG, 2016)
Computers are considered innovative in classrooms, raising expectations of increased cognitive learning outcomes or motivation with effects on Deeper Learning (DL). The "new medium", however, may cause cognitive overloads. Combined with gender-related variations in ability, self-efficacy or self-confidence, computers may even diminish learning effects. Our empirical study used a quasi-experimental design and the Intrinsic Motivation Inventory (IMI) to monitor efficacy in knowledge gain and motivation when using computer-aided versus textbook-based educational units. Our sample consisted of 393 eighth graders. One objective focused on gender effects associated with autonomous teacher-assisted learning via interactive software or an appropriate textbook. Both groups finished with a recapitulation with the teacher. A third group concluded a computer-aided lesson with a computer quiz. To provide evidence for DL we tested long-term memory after six weeks and examined its correlation with intrinsic motivation factors. In general, our intervention affected the girls' but not the boys' intrinsic motivation. We recorded significantly higher post-test scores in the textbook-based lesson, but the differences vanished in the retention test. The teacher-assisted consolidation phase increased long-term knowledge and positively intervened with the students' interest. Thus, we found evidence for DL.